THE POST TRAUMATIC RECOVERY OF ACHILLES TENDON FOR A PERFORMER ATHLETE - Elena Rata; Petru Ghervan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Getting great performance requires the athlete body a large amount of effort, that can lead to 'wear and tear' the body with irreversible damage to health, if not the whole process of sports training is conducted by proven scientific principles.